Fundraising with businesses - Waters, Joe (Wiley, 2014)
There's a reason why nonprofits are getting smaller checks from corporate giving programs. Companies are abandoning or slashing giving budgets and instead focusing on win-win pacts that drive sales and change the world. Nonprofits need guidance and practical know-how in this new age of mutually beneficial nonprofit and business partnerships